Citrus Flavonoids from Citrus reticulata Peels Potentially Target an Autophagy Modulator, MAP1LC3A, in Breast Cancer - Anggoro, Bayu; Kumara, Dennaya; Angelina, Dhella; Ikawati, Muthi (Indonesian Society for Cancer Chemoprevention, 2021)
Citrus flavonoids have been known for their vast biological activities including chemoprevention activities. However, the organic solvent extraction system limits its potential utilization. We recently adopted a hydrodynamic-cavitation method to extract citrus flavonoids from citrus peels. In this study we verified the high flavonoid content of the hydrodynamic-cavitation extract from Citrus reticulata peels and explore the potency of its citrus flavonoid contents as targeted chemoprevention agent for breast cancer by using bioinformatics. Based on a thin layer chromatography, the extract positively yielded high content of citrus flavonoids represented by hesperidin. The toxicity analysis by Protox II Online Tool revealed that hesperidin as the major citrus flavonoid in the extract was considered safe with a predicted LD50 of 12,000 mg/kg. We then further exploring citrus flavonoids’ capacity in targeting MAP1LC3A, a key protein in autophagy. UALCAN analysis validated that low expression of MAP1LC3A is associated with low survival rates in breast cancer patients. Limonin, hesperidin, narirutin, neohesperidine, and naringin are flavonoids from citrus peels that predicted to have inhibitory activity against Protein Kinase A (PKA), a negative upstream of MAP1LC3A, calculated by KNIME. Citrus flavonoids scoparone, cirsimaritin, 4',5,7-trimethoxyflavone, eupatorine, and hesperidin were also exhibit similar structure to an agonist of ATG4B, a protein that plays a role in MAP1LC3A activation. Furthermore, eupatorine, hesperidin, and cirsimaritin displayed a high affinity to ATG4B based on a molecular docking. We concluded that citrus flavonoids from citrus peels are safe to normal cells, and the citrus flavonoids potentially targets MAP1LC3A by inhibiting PKA and acting as ATG4B agonists. Thus, this extract-contained flavonoids from citrus peels is potential to be investigated further as a chemoprevention agent by inducing autophagy, especially for breast cancer.Keywords: Citrus reticulata, citrus flavonoid, autophagy, MAP1LC3A, breast cancer.